Isolamento, caracterização termodinâmica e estudos bioquímicos da lectina de sementes dormentes e de cotilédones de sementes germinadas da leguminosa Macrotyloma axillare - Marcos Aurelio de Santana (2008)
The Macrotyloma axillare seed lectin (LMA) is an N-acetyl-galactosamine (GalNac) specific lectin very important in biothecnology because the specific hemmaglutination by A1 human erythrocytes. In this work, the LMA from dormant and germinated was purified by precipitation techniques and ion exchange chromatography as a new purification technique. Such methodology yielded three LMA fractions (0.2, 0.3 and 0.4 M) with hemagglutinating activity on erythrocytes A1, being the LMA 0.2 the major fraction considering the mass yielding. The SDS-PAGE 12.5% and mass spectrometry analyses revealed a molecular mass about 28 1 kDa. The LMA hemmaglutinating activity is Ca(II) and Mn(II) dependent and the pH-dependent assays showed best hemagglutinating activity at pH 6.0-8.0; being decreased at acidic/alkaline conditions. The native molecular mass determination showed that the LMA is a tetramer at pH 6.0-8.0 range and a dimer at pH 4.0. The thermodynamic data obtained by ITC using GalNac and NO2-Phenyl-GalNac derivatives have shown that all the LMA fractions tested (from dormant and germinated seeds) are similar and the binding is enthalpically driven. The 2-NO2-Phenyl--D-GalNac ligand is the best ligand and good affinities can be obtained by titrations performed at low temperature (15°C) and high salt concentration (NaCl 1M). The LMA data from germinated seeds have shown that the LMA is a protein resistant to the germination process (120 hours) as it could be seen by mass spectrometry analyses and by ITC titrations. The LMA denaturation studies, provided by DSC, revealed high thermal stability (Tm) at pH 6.2 with melting temperature about 100°C. The LMA denaturation process is irreversible (two state model) and thermodynamically driven at the DSC conditions tested. The LMA germinated data and the high thermal stability for LMA corroborate that lectins are crucial proteins for metabolism, physiology and development events of the Macrotyloma axillare legume.